Enhancing Fourth Grade Learning Outcomes Through the Jigsaw Model with Styrofoam Media - Nasution, Afridah; Rahmi Seri Hanida; Novebri (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
This research aims to improve the learning outcomes of fourth-grade students through the application of the Jigsaw Model combined with styrofoam media in the learning of Theme 9 Subtheme 3. The background of this research is the low active participation of students and the limited variety of teaching methods used by teachers at SD Negeri 076 Kayu Jati Panyabungan. This research uses a quantitative approach with the classroom action research (CAR) method, which is carried out in two cycles. The subjects of the study are 30 students from class IVa. The data collection technique used was a learning outcome test, while data analysis was conducted using Microsoft Excel and SPSS version 21. The research results show that the average student learning outcomes in the pre-cycle were 87%, and there was a significant increase of up to 963% in cycle II. The independent sample t-test showed a calculated t-value of 13.59164, greater than the t-table value, indicating a significant difference in learning outcomes before and after the implementation of the model. These findings reinforce that the use of the Jigsaw Model with styrofoam media can effectively improve student learning outcomes. This study recommends the use of a cooperative learning model based on concrete media to enhance student engagement and understanding at the elementary school level.